2004
DOI: 10.1021/jm030982t
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Studies of Orexin A and Orexin B at the Human Orexin 1 and Orexin 2 Receptors Led to Orexin 2 Receptor Selective and Orexin 1 Receptor Preferring Ligands

Abstract: The neuropeptides orexin A and B (also known as hypocretins) play an important role in many physiological and behavioral activities. Orexins are ligands of two closely related G-protein-coupled receptors, that are the named orexin 1 and orexin 2 receptors. To clearly identify the minimal ligand sequences required for receptor activation, we synthesized and analyzed different centrally, C- and N-terminally truncated analogues of orexins A and B. Furthermore, we used the shortest active analogue to screen for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 24 publications
5
79
0
Order By: Relevance
“…Blue, nitrogen atoms; red, oxygen; yellow, sulfur; and green, fluorine. from orexin-A for activation of the receptor was similar between OX 1 and OX 2 (Ammoun et al, 2003;Lang et al, 2004 (Fig. 6B).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Blue, nitrogen atoms; red, oxygen; yellow, sulfur; and green, fluorine. from orexin-A for activation of the receptor was similar between OX 1 and OX 2 (Ammoun et al, 2003;Lang et al, 2004 (Fig. 6B).…”
Section: Discussionmentioning
confidence: 66%
“…Several researchers, who have investigated the determinants of orexin-A required to activate OX 1 and OX 2 using truncated peptides and alanine-scanned peptides (systematic replacement of the natural amino acids with L-alanine) (Ammoun et al, 2003;Lang et al, 2004Lang et al, , 2006Takai et al, 2006) have indicated that: 1) a minimal 19 amino acids of C-terminal segment of orexin-A (Arg15-Leu33) is required for OX activation, though functional activity of this peptide is reduced; 2) the replacement of orexin-A (Arg15-Leu33) truncated peptide residues, Leu16, Leu19, Leu20, His26, Gly29, Ile30, Leu31, Thr32, and Leu33 with alanine led to a significant reduction in the functional potency at the OX 1 (Darker et al, 2001); and 3) orexin-A distinctly recognized OX 1 from OX 2 and its binding to OX 1 required more molecular determinants than binding to OX 2 . Thus far, little is known about the OX ligand-binding pocket.…”
Section: Ethyl-2-[(6-methoxy-pyridin-3-yl)-(toluene-2-sulfonyl)-aminomentioning
confidence: 99%
“…Peptide Synthesis-The peptides were synthesized by solidphase technique on an automated multiple peptide synthesizer (Syro; MultiSynTech, Bochum, Germany) by using Rink amide resin (30 mg, resin loading 0.6 mmol/g) as described recently (23). The non-natural amino acids Abu, 3Abz, 4Abz, Acp, Aep, ␤Ala, 3Amb, 4Amb, Isn, and Ahx were coupled manually directly at the Rink amide resin (30 mg, resin loading 0.6 mmol/g) after removal of the Fmoc group with 30% piperidine in N,N-dimethylformamide twice for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The coupling reaction was performed twice with four equivalents of the Fmoc-protected un-natural amino acids, which were activated by 4 equivalents of 2-(1H-7-Azabenzotriazol-1-yl)-1,1,3,3-tetramethyl uronium hexafluorophosphate methanaminium and 8 equivalents of N,N-diisopropyl-ethylamin for 1 h. Completeness of the reaction was analyzed by a ninhydrin assay (24). The core segment wFw was synthesized as described previously (23). The peptide mimetics were cleaved from the resin in one step using trifluoroacetic acid, precipitated from ice-cold diethyl ether, washed, and finally lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide Synthesis. The inverse agonist peptides were synthesized by solid-phase technique on an automated multiple peptide synthesizer (Syro-MultiSynTech, Bochum, Germany) by using the Rink amide resin (30 mg; resin loading, 0.6 mmol/g) as described recently (Lang et al, 2004). All peptides were cleaved from the resin in one step with the use of TFA, precipitated from ice-cold diethyl ether, washed, and finally lyophilized.…”
Section: Methodsmentioning
confidence: 99%